2018
DOI: 10.1089/acm.2018.0085
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect and Potential Cumulative Benefit from Caudal Epidural D5W in Consecutive Participants with Chronic Low-Back and Buttock/Leg Pain

Abstract: Epidural D5W injection, in the absence of anesthetic, resulted in consistent postinjection analgesia and clinically significant improvement in pain and disability through 12 months for most participants. The consistent pattern postinjection analgesia suggests a potential sensorineural effect of dextrose on neurogenic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
2
19
0
1
Order By: Relevance
“…A therapeutic benefit of dextrose based on a neurogenic mechanism was proposed in 2008 36 hydrodissection for carpal tunnel syndrome, 31 peritendinous dextrose injection for Achilles tendinopathy, 37 and epidural dextrose for chronic low back pain. 38,39 Similar effects have been reported in a retrospective analysis of the results from regional hydrodissection using dextrose in patients with various neurogenic pain conditions of the upper body. 40 Several neural mechanisms have been hypothesized.…”
Section: Discussionsupporting
confidence: 65%
“…A therapeutic benefit of dextrose based on a neurogenic mechanism was proposed in 2008 36 hydrodissection for carpal tunnel syndrome, 31 peritendinous dextrose injection for Achilles tendinopathy, 37 and epidural dextrose for chronic low back pain. 38,39 Similar effects have been reported in a retrospective analysis of the results from regional hydrodissection using dextrose in patients with various neurogenic pain conditions of the upper body. 40 Several neural mechanisms have been hypothesized.…”
Section: Discussionsupporting
confidence: 65%
“…34 In a subsequent open-label study, the pattern and degree of pain relief with dextrose was similar after each injection, with a cumulative pain improvement of 3.4 ± 2.3 points (52%) on the 0-10 NRS scale for pain, and functional improvement 18.2 ± 16.4% (42%) on the 0-100 Oswestry Disability Index at 12 months. 35 The typical injectate volume for research on HD of the median nerve in the carpal tunnel is 10 mL or less. [1][2][3][4]7,8 However, according to the authors' experience, a much larger volume of injectate (typically 20-30 mL) needs to be used to completely release the nerve from the surrounding soft tissues to achieve an oval appearance, as most nerves and plexi are not located in such a confined area as the carpal tunnel.…”
Section: Non-cts-research Observations and Summary Of Research Statusmentioning
confidence: 99%
“…There was one level I study, which demonstrated epidural prolotherapy to be efficacious in relieving pain for up to 48 hours, but the results did not differ from placebo at 2 weeks . That same group assessed repeat injections as needed over the course of 1 year in the previous study cohort and found clinically significant improvement in NRS and ODI outcome measures . These studies highlighted the issues with single‐injection prolotherapy and the need to assess the effect of serial prolotherapy epidural injections for long‐term pain relief.…”
Section: Orthobiologics and The Literaturementioning
confidence: 99%